Business Challenges Such as Organizational Politics, Job Stress and Turnover Intentions of Employees: Implication for Policy Development in Ghana - Jnr, George Kankam; Suleman, Abdul-Razak (Journal of Asian Business Strategy, 2022)
The purpose of the study was to look at the link between Organizational Politics, Job Stress, and Turnover Intentions as some of the difficulties that face Ghanaian businesses, leading to policy formation. The participants in this study were Anglo Gold Ashanti employees. Data was gathered by the distribution of personally given questionnaires to respondents who were chosen using a non-probability sample approach called convenience sampling. In the end, a total of 100 completed questionnaires were employed in the study. The results of this study were established by analyzing the data with SPSS and Smart PLS SEM Software. The study's findings revealed that Organizational Politics and Turnover Intention had a substantial positive association. The outcomes of this study suggest that in order to lower turnover intentions, high levels of work stress and low levels of organizational politics must be addressed.